2020
DOI: 10.1101/2020.02.13.948158
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parallel alpine differentiation inArabidopsis arenosa

Abstract: Parallel evolution provides powerful natural experiments for studying repeatability of evolution. Well-documented examples from plants are, however, still rare, as are inquiries of mechanisms driving convergence in some traits while divergence in others. Arabidopsis arenosa, a predominantly foothill species with scattered morphologically distinct alpine occurrences is a promising candidate. Yet, the hypothesis of parallelism remained untested. We sampled foothill and alpine populations in all regions known to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 51 publications
3
26
0
Order By: Relevance
“…Previous genetic and phenotypic investigations and follow-up analyses presented here showed that the scattered alpine forms of both species represent independent alpine colonization in each mountain range, followed by parallel phenotypic differentiation (Fig. 1d, e) (43, 44). Thus, we sequenced genomes from seven alpine and adjacent foothill population pairs, covering all European lineages encompassing the alpine ecotype.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…Previous genetic and phenotypic investigations and follow-up analyses presented here showed that the scattered alpine forms of both species represent independent alpine colonization in each mountain range, followed by parallel phenotypic differentiation (Fig. 1d, e) (43, 44). Thus, we sequenced genomes from seven alpine and adjacent foothill population pairs, covering all European lineages encompassing the alpine ecotype.…”
Section: Introductionsupporting
confidence: 59%
“…Second, as genetic divergence often corresponds to the spatial arrangement of lineages 55 , external challenges posed by the alpine environment at remote locations may differ. Such risk is, however, mitigated at least in our Arabidopsis dataset, as the genomically investigated alpine populations share very similar niches 42 In contrast, no relationship between the probability of gene reuse and divergence was shown in experimental evolution of different populations of yeast 56 raising a question about the generality of our findings. Our study addresses a complex selective agent (a multihazard alpine environment 57 ) in order to provide insights into an ecologically realistic scenario relevant for adaptation in natural environments 14,53,54 ..…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…To characterize the extent of phenotypic and genotypic parallelism within a system, it is necessary to rigorously demonstrate that populations adapting to similar environments (collectively referred to as an ecotype) have arisen multiple times independently. We refer the reader to our previous analyses of parallel evolution in Senecio lautus (Roda et al, 2013b;James et al, 2020) and to systems such as the marine snail, Littorina saxatilis (Quesada et al, 2007;Johannesson et al, 2010;Bierne et al, 2013;Butlin et al, 2014;Pérez-Pereira et al, 2017), and the threespine stickleback, Gasterosteus aculeatus (Colosimo et al, 2005;Chan et al, 2010;Dean et al, 2019;Marques et al, 2019) where one can find some of the strongest evidence for the independent origin of populations, and to the increasing number of potential cases of parallel evolution in plants (Foster et al, 2007;Ostevik et al, 2012;Trucchi et al, 2017;Cai et al, 2019;Konečná et al, 2019;Knotek et al, 2020).…”
Section: A Framework To Measure Parallel Evolutionmentioning
confidence: 99%
“…Computational resources were provided by the CESNET LM2015042 and the CERIT Scientific Cloud LM2015085. This manuscript has been released as a pre-print at BioRxiv, https://doi.org/10.1101/2020.02.13.948158 ( Knotek et al, 2020 ).…”
mentioning
confidence: 99%